Optimal planting density of Agave for maximising aboveground biomass: A systematic literature review - Crawford, William; Tan, Daniel K. Y.; Van Ogtrop, Floris (Frontiers in Chemical Engineering, 2022)
There are hundreds of species of Agaves found globally in natural and anthropogenic systems. Agaves are used to produce fibres, alcoholic beverages like tequila, and in biofuel production. The objectives of this study were to assess the research available into Agave planting density and to use PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) to suggest an optimum planting density for the highest dry aboveground productivity. Background research into Agave planting densities found little data on the effect of planting density on biomass production, with most studies focusing on other independent variables affecting productivity. There were 13 data points included in the analysis. The meta-analysis suggested that the optimal planting density of Agave is approximately 2600 plants ha-1, which provides optimal dry aboveground biomass of 28.8 Mg ha-1 yr-1. These findings provide a framework for further experimentation in Australian conditions using a Nelder design density experiment to ground-truth the meta-analysis.